2015
DOI: 10.3329/seajph.v4i2.23694
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of goiter and iodine status among 6-12 years school age children in district Kohat, Pakistan

Abstract: Pakistan is considered to be one of the most severely iodine deficient countries in the region. A decade earlier, 70% of the population was estimated to be at risk of iodine deficiency. However, the recent use of iodized salt has reduced the intensity of the problem. Earlier studies regarding iodine deficiency in Pakistan were restricted to the northern mountainous regions, but have now been extended to the sub-Himalaya areas and the plains of Punjab. The aim of the present study was to investigate the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…36 Similarly, a few recent studies conducted in Charsadda, Kohat, and Karak districts of Khyber Pakhtunkhwa (KP) province reported goiter prevalences of 15.8%, 14.5%, and 35%, respectively, but the reported iodine deficiency prevalences reported, based on UIC, were higher at 54.7%, 92.7%, and 87.3%, respectively ( Table 2 ). 37 , 38 , 39 Equal numbers of studies (12) were conducted in KP and Punjab. However, half of the studies in Punjab (6) were concentrated around Lahore, and only a few reports came from other areas, while studies in KP were predominately conducted around Peshawar 4 (33.3%) and Swat 3 (25%) regions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Similarly, a few recent studies conducted in Charsadda, Kohat, and Karak districts of Khyber Pakhtunkhwa (KP) province reported goiter prevalences of 15.8%, 14.5%, and 35%, respectively, but the reported iodine deficiency prevalences reported, based on UIC, were higher at 54.7%, 92.7%, and 87.3%, respectively ( Table 2 ). 37 , 38 , 39 Equal numbers of studies (12) were conducted in KP and Punjab. However, half of the studies in Punjab (6) were concentrated around Lahore, and only a few reports came from other areas, while studies in KP were predominately conducted around Peshawar 4 (33.3%) and Swat 3 (25%) regions.…”
Section: Resultsmentioning
confidence: 99%
“…44 Both of these surveys highlighted the northern regions of the country as more affected by iodine deficiency. However, the studies conducted after the 2011 NNS showed severe iodine deficiency in terms of higher goiter prevalence (14%–35%) and mild-to-moderate iodine deficiency based on median UIC levels (75.18 μg/L, 89.9 μg/L, 62.3 μg/L and 56 μg/L in Peshawar, 45 Charsadda, 39 Karak, 37 and Kohat 38 districts, respectively) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And really, this is feasible in terms of support, affordability, acceptability by the people, inventory control etc. Lack of awareness of people about nutrient deficiency, its complications, low consumption of iron containing food, lack of effective education programs by planners and policy makers found in some similar study 20 demand immediate therapeutic and prophylactic program for correction of the nutritional anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan is known to be one of the severely iodine-deficient countries in the region [ 13 ]. In the past few years, studies carried out by the World Health Organization (WHO) provided an alarming picture of the country's profile for iodine deficiency disorders [ 14 ].…”
Section: Introductionmentioning
confidence: 99%